Search for exotic nuclear breakup configurations in Au+Au collisions - Sochocka, A.; Benisz, A.; Hachaj, P.; Nicolis, N. G.; Planeta, R.; Starypan, Z. (HNPS Advances in Nuclear Physics, 2020)
We study the feasibility of an experimental observation of toroidal breakup configurations in Au+Au collisions using the CHIMERA multidetector system. BUU simulations performed on the 197Au+197Au and 124Sn+124Sn systems indicate that the threshold energy for toroidal configuration formation decreases with increasing mass of the interacting system. For Au+Au collisions, this threshold energy is found around 20 MeV/nucleon. Static model simulations are also employed in order to explore the nature of reaction events involving a toroidal breakup configuration.